Kingdom of the Netherlands-Netherlands : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The staff report for the 2004 Article IV Consultation on the Kingdom of the Netherlands-Netherlands highlights the economic developments and policies. The economy is beginning to emerge from an extended downturn. Meanwhile, against a background of soft labor market conditions and economic slack generally, inflation pressures are low. The authorities acknowledged the economic reasoning behind these recommendations, but considered implementation politically difficult in light of a cultural preference for an egalitarian wage distribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet